Best Practice Principles for Business Incubators: A Comparison between South Africa and the Netherlands - MEYER, Natanya; MEYER, Daniel Francois; KOT, Sebastian (Journal of Advanced Research in Law and Economics; Vol 7 No 5 (2016): Vol 7, No 5(2016): JARLE Volume VII, Issue 5(19), Fall 2016, 2016)
Many researchers and industry leaders have identified business incubators as an alternative method to develop entrepreneurship and support small businesses. Incubators facilitate the success of a large number of start-ups and firms who, in turn, add value and growth to the economy. Eight factors that could influence the performance and success of incubators were identified in the literature. These factors include aspects such as management, infrastructure, networks and partnerships, mentoring, skills development and funding. The study followed a qualitative approach. Six incubator managers from South Africa (a developing country) and the Netherlands (a developed country) respectively, were interviewed to determine their views on factors for success. Incubators for small business development have been used for decades in the Netherlands but this process has only recently been introduced in South Africa. Despite this historical difference, incubator managers agree on most aspects, especially regarding the importance of networking, structured management, mentorship and training at incubators. The focus and funding factors of the incubators differed between the two countries. The implications of the research are that incubator managers from both countries could learn from each other and this research could be utilized to assess incubators in both developed and developing countries.
Keywords: best practice; business incubators; Entrepreneurship; Management; The Netherlands; South Africa